The Language Learning Strategies and Learning Styles of Beginning and Intermediate Learners in Indonesia - Patrisius Istiarto Djiwandono (TEFLIN Journal: A publication on the teaching and learning of English, 1998)
Abstract. The study aimed at finding out the patterns of strategies and the learning styles of intermediate and beginning learners in fluency and accuracy activities. The subjects were 27 second-year secretarial students at a university in Malang, Indonesia. Their scores on a C-test were used to separate them into two groups differing in English proficiency. Their strategies for learning English for oral communication were elicited by questionnaires, diaries, and inter-view. The analyses using one-way ANOVA showed that intermediate learnÃÂers were more diverse and more consistent in their strategies for fluÃÂency activities. They were also less inclined to visual and group learning than the beginning ones. Some implications and suggesÃÂtions for teaching English as a foreign language are then put forward.